Interaction between the 5-HT system and the basal ganglia: functional implication and therapeutic perspective in Parkinson's disease - Miguelez, Cristina; Morera-Herreras, Teresa; Torrecilla, Maria; Ruiz-Ortega, Jose Angel; Ugedo, Luisa (Frontiers in Neural Circuits, 2014)
The neurotransmitter serotonin (5-HT) has a multifaceted function in the modulation of information processing through the activation of multiple receptor families, including G-protein-coupled receptor subtypes (5-HT1, 5-HT2, 5-HT4-7) and ligand-gated ion channels (5-HT3). The largest population of serotonergic neurons is located in the midbrain, specifically in the raphe nuclei. Although the medial and dorsal raphe nucleus (DRN) share common projecting areas, in the basal ganglia (BG) nuclei serotonergic innervations come mainly from the DRN. The BG are a highly organized network of subcortical nuclei composed of the striatum (caudate and putamen), subthalamic nucleus (STN), internal and external globus pallidus (or entopeduncular nucleus in rodents, GPi/EP and GPe) and substantia nigra (pars compacta, SNc, and pars reticulata, SNr). The BG are part of the cortico-BG-thalamic circuits, which play a role in many functions like motor control, emotion, and cognition and are critically involved in diseases such as Parkinson’s disease. This review provides an overview of serotonergic modulation of the BG at the functional level and a discussion of how this interaction may be relevant to treating Parkinson’s disease and the motor complications induced by chronic treatment with L-DOPA.